Effectiveness of Education Through Digital Media to Improve Clean and Healthy Living Behavior (PHBS) Skills in Guidance Center Students in Malaysia - Maesaroh Lubis; Neni Nuraeni; Lilis Lismayanti; Mujiarto Mujiarto; Elfan Fanhas Fatwa Khomaeny; Asep Setiawan; Miftahul Falah (International Journal of Educational Research, 2025)
Digital transformation in health education opens up innovative opportunities to improve clean and healthy living behavior skills in the adolescent population. This study aims to analyze the effectiveness of education through digital media in improving clean and healthy living behavior skills in guidance studio students in Malaysia. The research method uses a mixed-method approach with a participatory action research design that integrates cooperative learning as the main strategy. The subjects of the study involved 32 students of Sanggar Bimbingan Kampung Pandan Malaysia consisting of 18 male students and 14 female students with an age range of 12-16 years. The intervention was carried out for 12 weeks using the "PHBS Digital Learning" application platform that integrates interactive multimedia features, quizzes, virtual simulations, and group discussion forums. Data collection was carried out through validated pre-test and post-test instruments with a Cronbach's Alpha reliability of 0.847. The results showed a significant increase in the composite knowledge score of 56.0% with a very large effect size (Cohen's d = 4.22), while practical skills increased by an average of 63.2% across all indicators. The digital platform facilitated 847 discussion posts with high engagement levels, reaching an average usage duration of 47.3 minutes per session. The transformation of student attitudes experienced a substantial increase from an average score of 2.3 to 4.2 on a scale of 1-5, with behavioral sustainability maintained by up to 78.1% of students in the follow-up evaluation. This study proves that digital media has high effectiveness in improving clean and healthy living behavior skills through the integration of cooperative learning and digital technology that creates a comprehensive and sustainable learning ecosystem.